Recasts and their use in second language development (2013)
This essay intends to review various research articles in order to describe a general idea about what has been found supporting the use of recasts and what has been found as negative evidence about its use. Recasts are one of the most useful methodological resources to provide feedback in SLA (Gass, et al..2003, cited by Nassaji, 2009. p.2) There are some researchers which have found the relative effect of recasts over other models of feedback (Long, et al., 1998), whether recasts promote learner uptake (Lyster and Ranta, 1997), whether recasts exposes learners to positive or negative evidence (Leeman, 2003). The use of recasts has better effects than modeling, any type of input enhancement, and elicitations; nevertheless, teachers should be selective regarding the type of error to which recasts are apply; facilitator, as feedback provider, and learner as receptor, are influenced by the nature of the conversation in which they are involved. As a consequence, output production after the recasts is forced by the apprehension the learner has.